KONTRIBUSI HASIL BELAJAR METODE PENELITIAN TERHADAP PERSEPSI KEMAMPUAN MENULIS SKRIPSI MAHASISWA PRODI PTB FT UNP - 745-756 , Lola Yulisman (Universitas Negeri Padang, 2015)
ABSTRACT This study aims to determine the contribution of learning outcomes Methods to perception Thesis writing skills Education of Program Building Engineering Faculty of Engineering, State University of Padang. This study is descriptive correlational. A total population of 87 students of the Faculty of Engineering Education Building, State University of Padang force from 2008 to 2010 with a sample of 30 students. Samples were taken with a probability sampling technique kind of simple random sampling. Data were collected using a questionnaire with Likert scale that uses five answer choices. The number of statements in the questionnaire as much as 60 point statement. Based on the analysis of correlation r values ​​obtained for 0.286 in the category of weak (low). As for the results obtained from the analysis of the contribution of squaring the correlation (r²) is obtained for 8.17%. The result of this contribution, it can be stated that the learning outcomes Research Methods course contribute as much as 8.17% to perception Thesis writing skills students of the Faculty of Engineering Education Building Padang State University. Keywords : Contributions , Results Learning , Perception Thesis Writing Ability